PERBANDINGAN ANTARA SRPMK DAN SISTEM GANDA PADA GEDUNG RUMAH SAKIT GIGI MULUT UNIVERSITAS UDAYANA - angganawibawa I Gusti; I Putu Ellsa Sarassantika; Ida Ayu Cri Vinantya Laksmi; I Wayan Gde Erick Triswandana; I Putu Deny Surastika Aditama (UKI Press, 2024)
Bali is one of the provinces that are destinations for foreign and domestic tourists. This causes Bali to follow developments in several sectors, one of which is the construction sector. Of course, every building in Bali must guarantee its safety and comfort. Especially in infrastructure buildings, the security of which must be guaranteed because it involves the safety of many people inside. For example, hospital buildings included in risk category IV need to pay attention to their deviations. For example, in the Udayana University oral dental hospital building which was previously planned using SRPMK, the design deviation value met the requirements or did not exceed the permit deviation. This oral dental hospital building will be re-planned using a dual system. So these two structural systems are chosen for comparison regarding the deviation values ​​between the two to provide information regarding which structural system is more optimal. In this writing, the analysis shows that the deviation value produced by the dual system is smaller than the special moment resisting frame system. Namely, with a maximum value of the double system of 8.96 mm and SRPMK with a maximum value of 21.696 mm with a clearance of 30.77 mm on the 2nd floor in the x direction and in the Y direction the maximum value of the double system is 12.60mm and SRPMK with the The maximum value is 20.07 mm with a permit of 26.92 mm on the 3rd floor.